Nutritional status in patients with liver cirrhosis - Łapiński, Tadeusz Wojciech (Clin Exp Hepatol, 2019)
AIM OF THE STUDY: To evaluate the nutritional status in patients with liver cirrhosis, depending on the stage of the disease. Fatty body mass, lean body mass and fluid content were determined, as well as basal metabolic rate. MATERIAL AND METHODS: The study included 56 patients with liver cirrhosis, aged 54 ±12 years. Nutritional status was determined with the BMI and albumin serum concentration. Fatty body mass, lean body mass and fluid content, as well as basal metabolic rate, were estimated by bioelectrical impedance, using a MALTRON 907 analyzer. RESULTS: Based on albumin concentration, malnutrition was diagnosed in over 80% of patients, usually (100%) in patients with liver cirrhosis belonging to Child-Pugh class C. In all patients, high energy demand was found in relation to basal metabolic rate. Average fatty body mass was comparable in all patients and ranged from 24 to 30%. Fluid content in the tissues was comparable in all evaluated groups and did not correlate with accompanying ascites. Fluid excess was found in 25% of Child-Pugh class A patients, in 59% of class B patients and in 60% of class C patients. CONCLUSIONS: Malnutrition is present in over 80% of patients with liver cirrhosis, and its frequency correlates with the stage of liver insufficiency. Patients with liver cirrhosis show high energy demand for basal metabolic processes. Fluid excess is mainly found in patients with more severe liver injury, but it does not correlate directly with ascites.